Oxidation of Phe454 in the Gating Segment Inactivates Trametes multicolor Pyranose Oxidase during Substrate Turnover - Halada, Petr; Brugger, Dagmar; Volc, Jindrich; Peterbauer, Clemens K; Leitner, Christian; Haltrich, Dietmar (PloS one, 2016)
The flavin-dependent enzyme pyranose oxidase catalyses the oxidation of several pyranose sugars at position C-2. In a second reaction step, oxygen is reduced to hydrogen peroxide. POx is of interest for biocatalytic carbohydrate oxidations, yet it was found that the enzyme is rapidly inactivated under turnover conditions. We studied pyranose oxidase from Trametes multicolor (TmPOx) inactivated either during glucose oxidation or by exogenous hydrogen peroxide using mass spectrometry. MALDI-MS experiments of proteolytic fragments of inactivated TmPOx showed several peptides with a mass increase of 16 or 32 Da indicating oxidation of certain amino acids. Most of these fragments contain at least one methionine residue, which most likely is oxidised by hydrogen peroxide. One peptide fragment that did not contain any amino acid residue that is likely to be oxidised by hydrogen peroxide (DAFSYGAVQQSIDSR) was studied in detail by LC-ESI-MS/MS, which showed a +16 Da mass increase for Phe454. We propose that oxidation of Phe454, which is located at the flexible active-site loop of TmPOx, is the first and main step in the inactivation of TmPOx by hydrogen peroxide. Oxidation of methionine residues might then further contribute to the complete inactivation of the enzyme.
Keywords: aktivace enzymů; Hydrogen Peroxide; molekulární konformace; Kinetics; Enzyme Activation; Phenylalanine; Substrate Specificity; sekvence aminokyselin; Methionine; peroxid vodíku; Molecular Sequence Data; Amino Acid Sequence; Molecular Conformation; hmotnostní spektrometrie; Carbohydrate Dehydrogenases; Models, Molecular; Trametes; oxidace-redukce; peptidy; molekulární sekvence - údaje; molekulární modely; fenylalanin; katalytická doména; Oxidation-Reduction; methionin; karbohydrátdehydrogenasy; Mass Spectrometry; Peptides; Enzyme Stability; substrátová specifita; kinetika; Catalytic Domain; stabilita enzymů